Human Beings and Social Structure in Frantz Fanon’s Philosophical Thought - Robertus Wijanarko; Valentinus Saeng (Jurnal Filsafat "WISDOM", 2022)
In response to the Colonial discriminative and exclusive concept of humanism, Frantz Fanon, an Algerian postcolonial thinker, proposes that the idea of humanism needs to be inclusive. To avoid the trap of the essentialist concept of humanism, Fanon argues that our understanding of human beings needs always to be connected with the existing social structure. By utilizing a postcolonial theory as a lens of analysis, this study will explore Frantz Fanon’s existential concept of human existence and investigate his philosophical-political thoughts. This exploration is driven by these critical questions: how is Fanon’s new understanding of the existential concept of human existence, which he proposes as a more inclusive concept? How does Fanon draw the correlation between human existence and social structure? What is the significance of his thoughts to critically investigate the socio-political structure in the postcolonial Indonesia? Our critical research will focus mainly on several of Fanon’s works: The Wretched of the Earth, Toward the African Revolution, and Black Skin White Masks. His other works will certainly be considered. We will utilize a litterer critical analysis method in approaching these works of Fanon. This new concept of Fanonian humanism, we argue, gives a theoretical frame and direction to develop existentially our understanding of an inclusive Indonesian humanism.